Markets drive the specialization strategies of forest peoples - Ruíz Pérez, M.; Belcher, B.; Achdiawan, R.; Alexiades, M.N.; Aubertin, C.; Caballero, C.J.; Campbell, Bruce M.; Clement, C.; Cunningham, A.B.; Fantini, A.C.; Foresta, H. de; García Fernandez, C.; et al. (2004)
Engagement in the market changes the opportunities and strategies of forest-related peoples. Efforts to support rural development need to better understand the potential importance of markets and the way people respond to them. To this end, we compared 61 case studies of the commercial production and trade of nontimber forest products from Asia, Africa, and Latin America. The results show that product use is shaped by local markets and institutions, resource abundance, and the relative level of development. Larger regional patterns are also important. High-value products tend to be managed intensively by specialized producers and yield substantially higher incomes than those generated by the less specialized producers of less managed, low-value products. We conclude that commercial trade drives a process of intensified production and household specialization among forest peoples.